Quantitative Detection of Horse Contamination in Cooked Meat Products by ELISA. (23rd November 2019) - Thienes, Cortlandt P; Masiri, Jongkit; Benoit, Lora A; Barrios-Lopez, Brianda; Samuel, Santosh A; Cox, David P; Dobritsa, Anatoly P; Nadala, Cesar; Samadpour, Mansour
Abstract: Concerns about the contamination of meat products with horse meat and new regulations for the declaration of meat adulterants have highlighted the need for a rapid test to detect horse meat adulteration. To address this need, Microbiologique, Inc., has developed a sandwich ELISA that can quantify the presence of horse meat down to 0.1% (w/w) in cooked pork, beef, chicken, goat, and lamb meats. This horse meat authentication ELISA has an analytical sensitivity of 0.000030 and 0.000046% (w/v) for cooked and autoclaved horse meat, respectively, and an analytical range of quantitation of 0.05–0.8% (w/v) in the absence of other meats. The assay is rapid and can be completed in 1 h and 10 min. Moreover, the assay is specific for cooked horse meat and does not demonstrate any cross-reactivity with xenogeneic cooked meat sources.